2019
DOI: 10.1111/anu.12948
|View full text |Cite
|
Sign up to set email alerts
|

Dietary choline requirement of juvenile olive flounder (Paralichthys olivaceus)

Abstract: An eight‐week study was conducted to determine the optimum dietary choline level in juvenile olive flounder, Paralichthys olivaceus. Seven diets were prepared to contain 0, 250, 500, 750, 1,000, 2,000 and 3,000 mg/kg diet. Juveniles (5.9 ± 0.03 g; 5.5 ± 0.4 cm; mean ± SD) were randomly distributed into 21 tanks (25 fish/tank) and fed one of the diets in triplicates. Survival rate of fish fed the diet containing the lowest choline level was significantly lower than those of fish fed the other diets (p < 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Two‐slope broken‐line regression and quadratic regression analysis between PWG against dietary choline levels indicated that the optimal choline requirements for maximum growth were estimated to be 3,254.1 and 6,488.3 mg/kg diet for L. vannamei , respectively. Some previous studies have demonstrated that two‐slope broken‐line model underestimates requirements, so quadratic model, broken quadratic model and saturation kinetic model may reflect the real requirements (NRC, 2011) This requirement value evaluated from the quadratic regression analysis was much higher than the study reported previously in fish such as hybrid tilapia Oreochromis niloticus × Oreochromis aureus (1,000 mg/kg diet, Shiau & Lo, 2000), R. canadum (695.9 mg/kg diet, Mai et al., 2009), M. amblycephala (1,198 mg/kg diet, Jiang et al., 2013), A. baerii (1,500 mg/kg diet, Yazdani Sadati et al., 2014) and olive flounder Paralichthys olivaceus (847 mg/kg diet, Won, Lee, Hamidoghli, Lee, & Bai, 2019). However, similar to the results observed in P. monodon (6,200 mg/kg diet, Shiau & Lo, 2001; 6,400 mg/kg diet, Shiau & Cho, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Two‐slope broken‐line regression and quadratic regression analysis between PWG against dietary choline levels indicated that the optimal choline requirements for maximum growth were estimated to be 3,254.1 and 6,488.3 mg/kg diet for L. vannamei , respectively. Some previous studies have demonstrated that two‐slope broken‐line model underestimates requirements, so quadratic model, broken quadratic model and saturation kinetic model may reflect the real requirements (NRC, 2011) This requirement value evaluated from the quadratic regression analysis was much higher than the study reported previously in fish such as hybrid tilapia Oreochromis niloticus × Oreochromis aureus (1,000 mg/kg diet, Shiau & Lo, 2000), R. canadum (695.9 mg/kg diet, Mai et al., 2009), M. amblycephala (1,198 mg/kg diet, Jiang et al., 2013), A. baerii (1,500 mg/kg diet, Yazdani Sadati et al., 2014) and olive flounder Paralichthys olivaceus (847 mg/kg diet, Won, Lee, Hamidoghli, Lee, & Bai, 2019). However, similar to the results observed in P. monodon (6,200 mg/kg diet, Shiau & Lo, 2001; 6,400 mg/kg diet, Shiau & Cho, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Choline supplementation also prevented signs of lipid malabsorption syndrome in post-smolt Atlantic salmon (Salmo salar L.) but had little effect on liver lipid metabolism (44) . In contrast, increasing dietary choline promoted higher liver lipid deposition and better growth in juvenile hybrid tilapia (Oreochromis niloticus × O. aureus) (45) , olive flounder (Paralichthys olivaceus) (4) , Japanese yellowtail (Seriola quinqueradiata) (23) .…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that cholesterol may be involved. Won et al ( 51 ) found that plasma cholesterol was significantly influenced by the graded choline levels in juvenile olive flounder ( Paralichthys olivaceus ) ( 51 ). Optimal cholesterol inhibited both canonical and non-canonical NF-kappaB pathways in grass carp kidney and spleen ( 6 ), which might support our hypothesis and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%